Investment Committee Paper on Keywords Studios - Michaelis, Maximilian (2024)
This project explores the leveraged buyout of Keywords Studios, a global leader in gaming outsourcing services. It evaluates the investment rationale, emphasizing the buy-and-build strategy, operational efficiency improvements driven by AI integration, and strategic geographic expansion. The financial analysis focuses on value creation drivers such as revenue growth, EBITDA margin improvements, cost synergies, and multiple arbitrage. Projected returns underscore the potential for significant value creation, culminating in an exit strategy through an IPO, strategic sale, or secondary sale. Keywords Studios’ market leadership and adaptability to industry trends solidify its position as a lucrative private equity investment.